PENGARUH PRODUKSI, HARGA EKSPOR, NILAI TUKAR, KEBIJAKAN GRATEKS-2/GERNAS, DAN BEA KELUAR TERHADAP EKSPOR KOMODITAS KAKAO SULAWESI SELATAN - Hasbiullah ; Prof. Dr. M. Pudjihardjo,Dr. Sasongko, SE, M.S.,,Dr. Iswan Noor, SE, M.E
The objective of this research is to analyze the influence of production,_x000D_ exports price, exchange rate, Grateks-2/Gernas policy, and export duties policy_x000D_ on cocoa exports in South Sulawesi using the data from 1986 until 2015. _x000D_ The purposes of this research are as follows: (1) to discover the_x000D_ significant influence of production on cocoa export in south sulawesi, (2) to_x000D_ discover the significant influence of export price on cocoa export in south_x000D_ sulawesi, (3) to discover the significant influence of exchange rate (Rupiah per_x000D_ US Dollar) on cocoa export in south sulawesi, (4) to analyze the significant_x000D_ influence of Grateks-2/Gernas policy on an increase of cocoa export in south_x000D_ Sulawesi, (5) to analyze the significant influence of export duties on the decline_x000D_ of cocoa export in south Sulawesi. _x000D_ This research uses the statistic quantitative approach with Engel-Granger’s_x000D_ Error Correction Model (ECM) analysis technique. _x000D_ The results of this research show that cocoa production, exports price,_x000D_ the long-terms and short-terms exchange rate have a positive influence, while_x000D_ the production rate have a significant influence on cocoa export in South_x000D_ Sulawesi which means, during the analysis time period, the production rate still_x000D_ shows a significant influence on cocoa bean exports. However, considering the_x000D_ data after 2010, the development of cocoa bean exports was in a decline since_x000D_ 2011. On the other hand, the production was in an increase at that time, there_x000D_ was a possibility if it were furtherly analyzed with more data, it could be_x000D_ concluded that the relationship of production with cocoa bean exports would be_x000D_ an opposite along with the growth of domestic industry. Later on, Grateks2/Gernas_x000D_ _x000D_ policy of cocoa shows a different result. This variable has a positive_x000D_ relationship in the long-term and negative relationship in the short-term and both_x000D_ of them do not have a significant influence nor there are evidences of it._x000D_ Meanwhile, the export duties have a negative and significant influence and it can_x000D_ be seen both in the long-term and in the short-term period which means that the_x000D_ government policy of PMK Number 067/PMK.011/2010 about by applying export_x000D_ duties which powerful enough to divert the cocoa bean exports to processed_x000D_ cocoa exports, which also can be seen from the development of processed_x000D_ cocoa production and the development of built-in capacity and also the_x000D_ investment on the processed cocoa production drastically increasing every year. _x000D_ Keywords : Production, Exports Price, Grateks-2/Gernas, Exchange Rate, _x000D_ Export Duties, Cocoa Exports, ECM